Women's Community Resilience in Facing Disasters through Participatory - Kusmawaty Matara (Universitas Aisyah Pringsewu, 2023)
The purpose of this study is to explore the strategic efforts made by Wire-G in improving the existence of the lives of Juriya village women and to find out post-mentoring changes through the Logwe analysis approach, encouraging women's independence and stimulating social change in the perspective of participatory empowerment. The type of research used is a type of qualitative descriptive research. This research uses an approach with a case study method. The result of this study is that the impact of floods and landslides has a major impact on women as a vulnerable community group, because they must lose gardens, houses, property. Strategic efforts made in empowering women are through gender mainstreaming programs in development through (1) strengthening local institutions in gender and environmental responsive planning and budgeting, (2) improving the quality of the environment and natural resources through sustainable agriculture, (3) empowering communities (especially women) based on local agricultural production.